PHYSICAL AND MECHANICAL PROPERTIES OF PASIR-PASIR WOOD (Xanthophyllum sp) FROM NORTH SUMATERA - Ahmad Dany Sunandar (Jurnal Pemuliaan Tanaman Hutan, 2007)
As a lasser know species, it is important to explore physical and mechanical properties of pasi-pasir (Xanthophyllum sp) wood. This research was conducted to observe physical and mechanical properties of pasir-pasir (Xanthophyllum sp) originated from North Sumatera. Sample were collected from North Tapanuli District, North Sumatera. Tree samples were divided into three sections and sampled for physical and mechanical test were collected from every section. The results revealed that this wood had medium density level. With respect to the radial and tangential shrinkage, the tested wood had a high shrinkage but T/R was still in permitted level. Wood strenght belonged to the strenght clas  V. The overall data of this wood properties suggested that the species is suitable for light constuction purposes and furniture.